Comparative analysis of synthesized silver nanoparticles using Madhuca longifolia and Pimenta dioica, for their antibiofilm activities. (2023) - kaithal, Poonam; Jain, Prashant A.; Archana,; Verma, Preetam
Abstract: The present study aims to compare the anti-biofilm activity of green synthesized silver nanoparticles by using the two indigenous plants Madhuca longifolia and Pimenta dioica . Among several metallic nanoparticles that are involved in biomedical application, silver nanoparticles (AgNPs) are engrossing all the attentions from researchers green synthesized AgNPs are most useful in the field of medicine. AgNPs are most useful because of small particles size, non-toxic effects and increased activity. Madhuca is the largest and widely distributed genus of the plant family Sapotaceae encompasses more than 110 species. The prepared nanoparticles were successfully characterized by using UV–vis spectroscopy, SEM, TEM, XRD, FTIR and Zeta potential. Further anti-bacterial and anti-biofilm activities of the synthesized AgNPs were determined. anti-bacterial and anti-biofilm activities were done against Gram positive bacteria ( Staphylococcus aureus ) and Gram negative bacteria ( Escherichia coli ). A comparative study was done between Madhuca longifolia and Pimenta dioica using two different microorganisms and found the Madhuca longifolia have better antibiofilm activity than Pimenta dioica . The study aimed to check and compare the antibiofilm activity of both the synthesized AgNPs because these plant sources have been traditionally used for many other applications apart from antibacterial action.